Shengu granules ameliorate ovariectomy-induced osteoporosis by the gut-bone-immune axis - Chen, Xiao cong; Li, Wei ju; Zeng, Jia ying; Dong, Yun peng; Qiu, Jian ming; Zhang, Bing; Wang, Dong yang; Liu, Jun; Lyu, Zhao hui (Frontiers in Microbiology, 2024)
Introduction Postmenopausal osteoporosis (PMOP) is a common chronic disease, and the loss of bone density and bone strength after menopause are its main symptoms. Effective treatments for PMOP are still uncertain, but Chinese medicine has some advantages in slowing down bone loss. Shengu granules are often used clinically to treat PMOP. It has been shown to be an effective prescription for the treatment of PMOP, and there is evidence that gut flora may play an important role. However, whether Shengu granules attenuate PMOP by modulating gut flora and related mechanisms remains unclear. Methods In this study, we mainly examined the bone strength of the femur, the structure of the intestinal microbiota, SCFAs in the feces and the level of FOXP3 cells in the colon. To further learn about the inflammation response, the condition of the mucosa and the level of cytokines in the serum also included in the testing. In addition, to get the information of the protein expression, the protein expression of OPG and RANKL in the femur and the protein expression of ZO-1 and Occludin in the colon were taken into account. Results The osteoporosis was significantly improved in the SG group compared with the OVX group, and the diversity of intestinal flora, the secretion level of SCFAs and the expression level of FOXP3 were significantly increased compared with the OVX group. In terms of inflammatory indicators, the intestinal inflammation scores of the SG group was significantly lower than those in the OVX group. Additionally, the serum expression levels of IL-10 and TGF-β in the SG group were significantly increased compared with the OVX group, and the expression levels of IL-17 and TNF-α were significantly decreased compared with the OVX group. In terms of protein expression, the expression levels of ZO-1, Occluding and OPG were significantly increased in the SG group compared with the OVX group, and the expression level of RANKL was significantly decreased compared with the OVX group. Discussion Shengu granules treatment can improve the imbalance of intestinal flora, increase the secretion of SCFAs and the expression of FOXP3, which reduces the inflammatory response and repairs the intestinal barrier, as well as regulates the expression of OPG/RANKL signaling axis. Overall, Shengu granules ameliorate ovariectomy-induced osteoporosis by the gut-bone-immune axis.